The youth movement of Galicia at the end of the XIXth - 30th of the XXth centuries in the modern research studies of Ukraine - Kolybabyuk, Svitlana (Skhid, 2013)
In this article reviews the historiography of modern scientific research achievements of the youth movement of the late nineteenth ofGalicia- 30th years of twentieth century. The writer states that generalize the work, which comprehensively reviewed their development work on the history of individual societies, studies of specific areas of their activities, historical and biographical and other different genres publication is a significant contribution to the development of modern historiography of the problem.